Geriatric Assault Victims Treated at U.S. Trauma Centers: Five-Year Analysis of the National Trauma Data Bank - Rosen, Tony (Injury, 2016)
INTRODUCTION: While geriatric trauma patients have begun to receive increased attention, little research has investigated assault-related injuries among older adults. Our goal was to describe characteristics, treatment, and outcomes of geriatric assault victims and compare them to geriatric victims of and younger accidental injury assault victims. PATIENTS AND METHODS: We conducted a retrospective analysis of the 2008–2012 National Trauma Data Bank. We identified cases of assault-related injury admitted to trauma centers in patients aged ≥60 using the variable “intent of injury.” RESULTS: 3,564 victims of assault-related injury in patients aged ≥60 were identified and compared to 200,194 geriatric accident victims and 94,511 assault victims aged 18–59. Geriatric assault victims were more likely than geriatric accidental injury victims to be male (81% vs. 47%) and were younger than accidental injury victims (67±7 vs. 74±9 years). More geriatric assault victims tested positive for alcohol or drugs than geriatric accident victims (30% vs. 9%). Injuries for geriatric assault victims were more commonly on the face (30%) and head (27%) than for either comparison group. Traumatic brain injury (34%) and penetrating injury (32%) occurred commonly. The median injury severity score (ISS) for geriatric assault victims was 9, with 34% having severe trauma (ISS≥16). Median length of stay was 3 days, 39% required ICU care, and in-hospital mortality was 8%. Injury severity was greater in geriatric than younger adult assault victims, and, even when controlling for injury severity, in-hospital mortality, length of hospitalization, and need for ICU-level care were significantly higher in older adults. CONCLUSIONS: Geriatric assault victims have characteristics and injury patterns that differ significantly from geriatric accidental injury victims. These victims also have more severe injuries, higher mortality, and poorer outcomes than younger victims. Additional research is necessary to improve identification of these victims and inform treatment strategies for this unique population.